Analisis Pengaruh Loan To Deposit Ratio, Debt To Equity Ratio dan Return On Investment Terhadap Net Interest Margin (Studi Kasus pada Bank Konvensional Tahun 2014-2018) - Budi Junaedi (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This study aims to analyze the effect of the loan to deposit ratio variable, debt to equity ratio and return on investment to net interest margins. Research in I took conventional banks listed on the Indonesia Stock Exchange as the subject of research. Data were analyzed statistically through panel data regression analysis with the help of the Eviews program. The results of the analysis show that: (1) Loan to deposit ratio has a significant influence on net interest margin, (2) Debt to equity ratio does not have a significant effect on net interest margin, and (3) Return on investment has a significant effect on net interest margin. Simultaneously, the three independent variables have a significant effect on the net interest margin.